Ethos in Multimodal Persuasive Texts : Os outdoors nas eleições portuguesas - Topete de Oliveira Pita, Sara; Da Silva Baptista, Dina Maria (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
In this article, we analyze 19 billboards of presidential candidates for the Lisbon and Porto City Councils in the 2021 Municipal Elections in Portugal. Taking as a reference one of the three axes of the Grammar of Visual Design (GDS), we intend to study the compositional level of this persuasive genre. The present work focuses on the visual composition, specifically the actor/candidate and the graphic stain, and on linguistic features, embodied in the slogan (verb moods and tenses and their relationship with speech acts, lexical choices, argumentative construction, among others), fundamental contributions to the creation of the ethos.